2007
DOI: 10.3892/ijo.31.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of VEGF and TGF-β1 mRNA in Pap smears correlates with progression of cervical intraepithelial neoplasia to cancer: Implication of YY1 in cervical tumorigenesis and HPV infection

Abstract: Abstract. The screening of neo-angiogenesis related gene expression has uncovered many disrupted molecular pathways which may significantly confer to malignant transformation of various cell types including cervical cells. The objective of the present study was to delineate whether changes in certain gene expression profiles during the malignant conversion of the uterine cervix can be potentially used to predict the clinical course and outcome of the cervical pathology. Total RNA was isolated from Pap smears o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 47 publications
7
51
0
4
Order By: Relevance
“…The putative role of YY1 in tumorigenesis is supported by its known interaction in the cell cycle regulation 4 and, accordingly, many studies were conducted to evaluate the involvement of YY1 in several solid tumor types. [14][15][16][17][18][19] In this study we have provided evidence that YY1 is expressed at significantly higher levels in high-grade lymphomas, including Burkitt's Lymphoma and DLBCL, when compared to normal B cells. DLBCL is the most frequent non-Hodgkin's lymphoma subtype, accounting for 30% to 35% of all lymphoma cases.…”
Section: Discussionmentioning
confidence: 82%
“…The putative role of YY1 in tumorigenesis is supported by its known interaction in the cell cycle regulation 4 and, accordingly, many studies were conducted to evaluate the involvement of YY1 in several solid tumor types. [14][15][16][17][18][19] In this study we have provided evidence that YY1 is expressed at significantly higher levels in high-grade lymphomas, including Burkitt's Lymphoma and DLBCL, when compared to normal B cells. DLBCL is the most frequent non-Hodgkin's lymphoma subtype, accounting for 30% to 35% of all lymphoma cases.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the authors showed that the increase of YY1 at both transcript and protein levels were associated with the presence of Human Papilloma Virus (HPV) infection indicating that YY1 may play an important role in the malignant transformation. 22 YY1 overexpression has been documented also in human osteosarcoma. 23 The authors, using different approaches, demonstrated that YY1 is overexpressed in osteosarcoma cell lines and tissues compared to normal osteoblastic cells with a predominant localization in the nucleus.…”
Section: Implication Of Yin Yang 1 In Response To Therapeutic-inducedmentioning
confidence: 95%
“…Elevated YY1 protein levels are associated with a number of cancer types such as high-grade squamous cervical intraepithelial lesions, cervical cancer and HPV infection of the cervix (16). This has led to the suggestion that YY1 may serve as a diagnostic and prognostic tumor marker, and a drug target in cancer therapy (11).…”
Section: Discussionmentioning
confidence: 99%